2009
DOI: 10.1007/s10926-009-9162-7
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated and Tailored Work Rehabilitation: A Randomized Controlled Trial with Economic Evaluation Undertaken with Workers on Sick Leave Due to Musculoskeletal Disorders

Abstract: Introduction In Denmark, the magnitude and impact of work disability on the individual worker and society has prompted the development of a new ''coordinated and tailored work rehabilitation'' (CTWR) approach. The aim of this study was to compare the effects of CTWR with conventional case management (CCM) on return-towork of workers on sick leave due to musculoskeletal disorders (MSDs). Methods The study was a randomized controlled trial with economic evaluation undertaken with workers on sick leave for 4-12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
2
9

Year Published

2011
2011
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(128 citation statements)
references
References 27 publications
4
113
2
9
Order By: Relevance
“…Many studies have evaluated the effectiveness of return to work (RTW) interventions after injury and illness (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These have ranged from minimal postal intervention, OH phone intervention to multidisciplinary approaches involving workplace assessment, work modifications and importantly case management involving all stakeholders (22)(23)(24)(25).…”
Section: Brown Et Almentioning
confidence: 99%
“…Many studies have evaluated the effectiveness of return to work (RTW) interventions after injury and illness (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). These have ranged from minimal postal intervention, OH phone intervention to multidisciplinary approaches involving workplace assessment, work modifications and importantly case management involving all stakeholders (22)(23)(24)(25).…”
Section: Brown Et Almentioning
confidence: 99%
“…Most RTW interventions focus on specific target groups, mostly sick-listed individuals with musculoskeletal health problems (3)(4)(5)(6)(7)(8)(9)(10), whereas RTW interventions addressing mental health problems are scarce (11,12). A recent systematic review of the effectiveness of RTW interventions for persons sick-listed due to musculoskeletal problems concluded that most interventions appeared beneficial.…”
mentioning
confidence: 99%
“…The Danish national RTW program is funded with 32 million euros from the Danish National Prevention Fund and 4.3 million euros from the Ministry of Employment and includes 21 of the 98 Danish municipalities. The Danish National Research Centre for the Working Environment (NRCWE) was appointed to develop the Danish RTW program in accordance with the action plan, existing sickness management legislation, and previous experiences from national and international intervention studies (9,13).…”
Section: Aust Et Almentioning
confidence: 99%